Impactos do manejo de um sistema plantio direto no crescimento e produtividade do arroz de terras altas e feijão de inverno em sucessão e nos atributos do solo - Nascimento, Vagner do [UNESP] (2015)
The planning succession allied cover crops in the off-season and sporadic mechanical decompression are options to minimize compaction soil surface under, as well as directly providing improvements in soil attributes in no-tillage system (NTS) deployed in the Savannah South Mato Grossense, advocating the sustainability of the production system. The objective was to evaluate the mechanical soil decompression, development and yield of cover crops in the spring in NTS, and also in the growth and yield of rice crop upland and common bean winter in succession, in addition to changes in chemical and physical attributes of the soil, after each cultivation of annual crops. The study was conducted in Selvíria, MS, in 2012/13 e 2013/14, in a Savannah South Mato Grossense, Oxisol, clayey, in a randomized block design arranged in a factorial design 5x2 for rice and common bean, with four replications. The treatments were a combination of five cover crops (fallow (control), Cajanus cajan, Crotalaria juncea, Pennisetum glaucum and Urochloa ruziziensis) with and without mechanical soil scarification. The species of Pennisetum glaucum, regardless of chiseling in NTS promoted greater dry matter yield and accumulation of macronutrients in the shoot as well as greater persistence of plant debris; the chiseling in NTS and the previous cropping Cajanus cajan provided higher yields of rice in the first year, but did not influence the rice yield in the second year; crops predecessors Crotalaria juncea and Pennisetum glaucum with scarification, followed by rice cultivation, provided increases in bean commun yield winter in succession; the off-Pennisetum glaucum, Crotalaria juncea and Urochloa ruziziensis independent of scarification Urochloa ruziziensis provided improvements more frequently in chemical attributes in the soil profile; the chiseling in NTS promoted greater porosity, and reduced the density and soil ...